A complete and dynamic tree of birds - Emily Jane McTavish; Jeff A. Gerbracht; Mark T. Holder; Marshall J. Iliff; Denis Lepage; Pamela C. Rasmussen; Benjamin D. Redelings; Luna L. Sánchez Reyes; Eliot T. Miller (Proceedings of the National Academy of Sciences, 2025)
We present a complete, time-scaled, evolutionary tree of the world’s bird species. This tree unites phylogenetic estimates for 9,239 species from 262 studies published between 1990 and 2024, using the Open Tree synthesis algorithm. The remaining species are placed in the tree based on curated taxonomic information. The tips of this complete tree are aligned to the species in the Clements Taxonomy used by eBird and other resources, and cross-mapped to other taxonomic systems including the Open Tree of Life (Open Tree), National Center for Biotechnology Information, and Global Biodiversity Information Facility. The total number of named bird species varies between 10,824 and 11,017 across the taxonomy versions we applied (v2021, v2022, and v2023). We share complete trees for each taxonomy version. The procedure, software, and data stores we used to generate this tree are public and reproducible. The tree presented here is Aves 1.3 and can be easily updated with new phylogenetic information as new estimates are published. We demonstrate the types of large-scale analyses this data resource enables by linking geographic data with the phylogeny to calculate the regional phylogenetic diversity of birds across the world. We will release updated versions of the phylogenetic synthesis and taxonomic translation tables annually. The procedure we describe here can be applied to developing complete phylogenetic estimates for any taxonomic group of interest.